The effect of Bacillus probiotic on growth performance and fecal consistency of growing-finishing pigs - Nitikanchana, S.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,099 pigs (PIC 1050 × 337; initially 75 lb) were used in a 104-d study to determine the influence of a Bacillus product and diet type on growth performance, carcass traits, fecal consistency, and pen cleaning time in growing-finishing pigs raised under commercial conditions. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 6 dietary treatments in a completely randomized design with 26 to 27 pigs per pen and 7 replications per treatment. Treatments were arranged as a 3 × 2 factorial with main effects of Bacillus product (0, 1x, or 10x) and diet type (corn-soybean meal or a by-product diet with 30% dried distillers grains with solubles [DDGS] and 20% bakery). The dose of Bacillus in the diet was approximately 200 million cfu/g feed for the 1x level and 2 billion cfu/g feed for the 10x level. Fecal consis- tency and manure buildup in each pen was scored at the end of the trial by 3 observers with the average value per pen used for analysis. Time required to wash each individual pen was also recorded. Overall (d 0 to 104), no differences were found in growth performance or carcass composition for pigs fed the Bacillus product; however, pigs fed the 1x level of Bacillus tended (quadratic, P = 0.10) to have the lowest ADG. Manure texture score tended to increase (linear, P = 0.07) as Bacillus dose increased, indicating that pigs fed the Bacillus product had firmer stools. For diet formulation, pigs fed the diet containing by-prod- ucts had increased (P = 0.01) ADFI compared with pigs fed the corn-soybean meal diet. With no difference in ADG, feed efficiency was poorer (P < 0.01) for pigs fed by-product diets. Pens that contained pigs fed by-product diets required more (P < 0.01) time to wash, which appeared to be the result of looser manure texture (P = 0.09) and increased (P = 0.08) manure buildup in pens where pigs were fed by-product-based diets. The Bacillus product tested did not improve growth performance, but altered fecal consistency and barn wash time.
Keywords: Swine; Bacillus; By-products; Fecal consistency; Finishing pig; Wash time